Isolation and characterization of a novel Rhabdovirus from a wild boar (Sus scrofa) in Japan - Sakai, Kouji; Hagiwara, Katsuro; Omatsu, Tsutomu; Hamasaki, Chinami; Kuwata, Ryusei; Shimoda, Hiroshi; Suzuki, Kazuo; Endoh, Daiji; Nagata, Noriyo; Nagai, Makoto; Katayama, Yukie; Oba, Mami; et al. (Veterinary microbiology, 2015)
•A novel virus (WBRV1) was isolated from wild boar.•WBRV1 belongs to a new genus of Rhabdoviridae.•Neutralizing antibodies were found in domestic pigs and wild Sika deer. A novel rhabdovirus was isolated from the serum of a healthy Japanese wild boar (Sus scrofa leucomystax) and identified using the rapid determination system for viral nucleic acid sequences (RDV), next-generation sequencing, and electron microscopy. The virus was tentatively named wild boar rhabdovirus 1 (WBRV1). Phylogenetic analysis of the entire genome sequence indicated that WBRV1 is closely related to Tupaia rhabdovirus (TRV), which was isolated from cultured cells of hepatocellular carcinoma tissue of tree shrew. TRV has not been assigned to any genus of Rhabdoviridae till date. Analysis of the L gene indicated that WBRV1 belongs to the genus Vesiculovirus. These observations suggest that both TRV and WBRV1 belong to a new genus of Rhabdoviridae. Next-generation genome sequencing of WBRV1 revealed 5 open reading frames of 1329, 765, 627, 1629, and 6336 bases in length. The WBRV1 gene sequences are similar to those of other rhabdoviruses. Epizootiological analysis of a population of wild boars in Wakayama prefecture in Japan indicated that 6.5% were positive for the WBRV1 gene and 52% were positive for WBRV1-neutralizing antibodies. Furthermore, such viral neutralizing antibodies were found in domestic pigs in another prefecture. WBRV1 was inoculated intranasally and intraperitoneally into SCID and BALB/c mice and viral RNA was detected in SCID mice, suggesting that WBRV1 can replicate in immunocompromised mice. These results indicate this novel virus is endemic in wild animals and livestock in Japan.